Negotiating with the "Archenemy": The Ethics of the Croatian and Slavonian Nobility at the Christian-Ottoman Border - Štefanec, Nataša (Array, 2014)
In the 16th and partly in the 17th century, the Croatian and Slavonian nobility often threatened the Habsburgs with surrender to the Ottomans, especially in times of fierce combats. Other social strata, the peasants and the military, even voluntarily changed sides and accepted the jurisdiction of a more amenable overlord in their attempt to survive. Their interactions with the Ottomans therefore cannot be characterised as merely confrontational. Actually, conditioned by an attempt to avoid devastation and annihilation, the opposing sides were engaged in various types of rather complex interactions and thus challenged the paradigm of antemurale Christianitatis. This paper addressed two main issues. Firstly: were the threats of surrender to the Ottomans a plausible political option in the Croatian-Slavonian Kingdom? Secondly, the question as to whether the Ottomans can be seen as the principal adversaries of the Croatians and Slavonians during the early modern period, the archenemy of Christianity. Paper scrutinised everyday practices of interactions with the Ottomans at the Military Border as well as forms of negotiations of different representatives with the Ottomans.